Pengelolaan SDM Pendidikan di PAUD Al - Qur'an Al - Jaami'ah - Al-Husen, Putri Lailiyatul Azizah; Putri Hoyrun Nisa Amini; Salsabila Wiyosa Sagita; Siti Nurul Rahmah; Hinggil Permana (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
The main aim of PAUD institutions, which are early childhood education organizations, is to develop students' intelligence. Implementation requires not only planning teaching and learning activities but also an integrated strategy that considers a number of variables, including educational objectives, teachers, students, facilities and the environment. PAUD institutions must pay attention to the human resources (HR) they have. Management of these institutions requires increasing the knowledge, skills and abilities of human resources. This research focuses on human resource management in education, especially in terms of teaching and education staff. By maintaining a conservation HR commitment, you can encourage work morale, provide inspiration, and increase employee productivity in the organization through effective strategic management.